The transfer from perceptual-cognitive skills training of anticipatory judgments to field and anxiety conditions in elite athletes - Alder, D. B.; Ford, P. R.; Causer, J.; Williams, A. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Anticipatory judgments and the visual search strategies used to make them are a key part of expert sports performance. Researchers have shown these judgements can be improved through laboratory-based training (Hagemann et al., 2006). However, they are yet to examine whether these laboratory-based improvements transfer to the field or to anxious conditions. The aim of this study was to examine the transfer from perceptual-cognitive skills training of anticipatory judgements in the laboratory to the field and to anxious conditions for elite badminton players. Method: Participants were 16 international badminton players assigned to either a training group or a control group in a pre-acquisition-post-test design. In pre- and post-tests, both groups completed a laboratory and field-based temporal occlusion test in which they anticipated serve direction under high and low anxiety conditions. In acquisition between tests, the training group received a perceptual-cognitive training intervention detailing the "gold standard" visual search used by Olympic players with trial-by-trial video feedback on their performance, whereas the control group did not. A mobile eye tracker was worn throughout to collect visual search behaviour. Anticipation judgment accuracy and visual fixations were analysed in ANOVA. Results: In the laboratory pre-test, there were no between-group differences in judgement accuracy (66 %) or final visual fixation duration (1829 ms), but accuracy was lower and final fixation shorter in the high compared to low anxiety condition. In the laboratory post-test, the training group made more accurate judgements (79 %) and had a longer final fixation (2293 ms) compared to both their pre-test (68 %; 1848 ms) and the control group (63 %; 1877 ms) under both high and low anxiety conditions, albeit judgements were less accurate and final fixations were shorter in the high anxiety conditions. In the field pre-test, there were no between-group differences in judgement accuracy (82 %); whereas in the post-test the training group made more accurate judgments (87 %) compared to the control group (78 %). Discussion: Perceptual-cognitive skills training increased the accuracy of anticipatory judgements compared to control, supporting previous research (Hagemann et al., 2006). The improvements in anticipatory judgments from the training in the laboratory transferred to improved judgments in the field, when compared to control, but did not transfer to anxious conditions. Findings show how training programmes can be created to improve anticipatory judgments in the field and for anxiety-inducing conditions.